DAMPAK WISATA PANTAI LONMALANG TERHADAP SOSIAL EKONOMI MASYARAKAT DI KABUPATEN SAMPANG KECAMATAN SOKOBANAH - Ahmad Ramadhan; Muhammad Faisal Abdullah (Jurnal Ilmu Ekonomi JIE, 2019)
This study aims to determine the impact of the existence of lon malang beach tourism on the socobenah sub-district socio-economic community of sampang district. This research is a qualitative descriptive study. The variables used in this study are socio-economic community, economic activities, access, employment opportunities and land use change. The sample used in this study was the people around Lonamalang village. Data analysis techniques using the questionnaire method, namely by making a list of written questions that have been prepared previously and provide answer choices (closed questionnaire) or provide an opportunity for respondents to answer freely and carried out by distributing questionnaires to respondents. Qualitative analysis is used to determine the socio-economic problems of the community, access, land conversion, and employment opportunities. The results of this study indicate that the existence of poor Lon beach tourism has an impact on the social economy of the community, economic activities, employment opportunities. Keyword: Social-economic, Lonmalang beach tourism